Parallel Label‐Free Isolation of Cancer Cells Using Arrays of Acoustic Microstreaming Traps. Issue 2 (11th December 2018) - Lu, Xiaolong; Martin, Aida; Soto, Fernando; Angsantikul, Pavimol; Li, Jinxing; Chen, Chuanrui; Liang, Yuyan; Hu, Junhui; Zhang, Liangfang; Wang, Joseph
Abstract: A new parallel label‐free isolation platform for isolating cancer cells (>10 µm) from biological samples using an array of acoustic microstreaming traps is demonstrated. The new microstreaming trapping platform offers high isolation efficiency and treatment in spiked diluted (1:2) blood samples without labeling, extra processing steps or sheath flows (common to other label‐free cell‐separation methods), hence, simplifying the microfluidic set‐up and operation. The versatility of this label‐free method is illustrated by the size‐dependent isolation of synthetic colloids and by three different models of breast cancer cells, showing a remarkably high isolation efficiency (95 ± 5%), being ≈100% for MCF‐7. Extensive experimental data and theoretical simulations confirm that the local acoustic microstreaming produced by the micropillar trap can discriminate and isolate microparticles based solely on their size. Moreover, the parallel isolation generated by the trap array arrangement is capable of effectively improving the capturing efficiency. The tunable and reversible properties of the acoustic microstreaming allow for cell capturing and optical detection within the trapping area, followed by cell release, enrichment, and collection for further studies. This label‐free trapping strategy can open numerous new opportunities for rapid and sensitive detection and capture of cancer cells in biological samples for meaningful clinical applications. Abstract : A label‐free parallel isolation platform for isolating circulating cancer cells using an array of acoustic microstreaming traps is presented. The microtraps can discriminate and isolate microparticles based solely on their size. The versatility of this method is demonstrated using three different types of model breast cancer cells, showing a remarkably high isolation efficiency.